Doctoral dissertations on second language writing and technology in the USA (2010–2019). (April 2021) - Gibbons, John; Li, Mimi
Abstract: This paper reviews 20 representative Ph.D. dissertations on second language (L2) writing and technology completed in the USA over the past decade (2010–2019). These dissertations were selected using advanced search via ProQuest Dissertations & Theses. Five thematic categories were examined: (1) computer-mediated teacher/peer feedback; (2) automated writing evaluation; (3) computer-based collaborative writing; (4) technology-based writing instruction/assessment; and (5) digital composing/literacy. Each dissertation study was closely reviewed, with the presentation of illustrative tables. After analyzing and discussing the research designs, findings, and contributions of these studies, the authors identified the research trend and highlighted directions for future dissertation research in the field of L2 writing and technology.